Review Of Secure And Privacy Preserving DRM Scheme - Bhavana S, Rote; Deshpande, MM (International Journal of Computer Sciences and Engineering, 2025)
Digital rights management (DRM) is becoming a key enabling technology to protect intellectual property of digital contents and it controls dissemination and usage of digital content. Numerous researches have been conducted for DRM since the past decade. This paper summarizes the basic concepts in DRM and present the typical DRM reference architecture. Secondly, requirements in this domain are studied. Furthermore, the some existing techniques are presented with detail analysis to point out the advantages and disadvantages respectively.